An Assessment Of Parental Involvement In Learner Retention In Public Primary Schools Of Malindi Sub - County In Kilifi County, Kenya - Kirimi, Josephine Kagwiria; Muteti, Daudi Muthoka (European Scientific Journal, ESJ, 2016)
Despite the Kenya government re-introducing free primary education, some school age children are still locked out of school whereas dropout and repetition continue to be pervasive. The study found out that retention rates in public primary schools in central zone of Malindi sub-county, Kenya had declined and the dropout rate was on the increase. The most prominent causes of the declining rates of access and retention of pupils in public primary schools in the zone were, illiteracy, poverty, early pregnancy, grade repetition and tourism activities. The study recommends that the government enforce adherence of the laid down policies to enhance learner retention in education. The government should also put up adult education centres to help improve literacy levels among parents.